A simple method to prepare superhydrophobic and regenerable antibacterial films. (13th May 2020) - Liang, Xiaomei; Chen, Xin; Zhu, Jianli; Liu, Lixian; Wang, Wei; Wang, Xu; Qu, Chunsheng
Abstract: Macromolecules incorporating N-halamines have shown significant antibacterial properties and can be regenerated by chlorination. In this work, a new type of regenerable material made of nano-sized latex particles having N-H groups was prepared via the emulsion polymerization of methacrylamide and dodecafluoroheptyl methacrylate with divinylbenzene as a crosslinker. The N-H moieties in this polymer were subsequently transformed into N-Cl groups by chlorination with an aqueous sodium hypochlorite solution, and films were prepared by casting on substrates previously coated with a self-adhesive silicone rubber. The nanoparticles and the films were characterized by Fourier transform infrared (FTIR) spectroscopy, x-ray photoelectron spectroscopy (XPS), thermogravimetric analysis (TGA), contact angle measurements, scanning electron microscopy (SEM) and microbiological tests. The results showed that F and Cl were successfully incorporated in the nanoparticles, that the films were thermally stable and hydrophobic (with a contact angle of 152°), and that these materials exhibited antimicrobial properties. The N-Cl groups killed bacteria by releasing active chlorine as they transitioned to N-H groups, and could be re-chlorinated with a methanol solution of isocyanuric chloride. FTIR and XPS analyses confirmed this regeneration, while SEM image showed that the morphology of the original microspheres was maintained after re-chlorination. The re-chlorinated films also maintained superhydrophobic and bactericidal characteristics.